2012
DOI: 10.1186/2110-5820-2-44
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of systemic, hepatosplanchnic, and microcirculatory perfusion parameters with 6-hour lactate clearance in hyperdynamic septic shock patients: an acute, clinical-physiological, pilot study

Abstract: BackgroundRecent clinical studies have confirmed the strong prognostic value of persistent hyperlactatemia and delayed lactate clearance in septic shock. Several potential hypoxic and nonhypoxic mechanisms have been associated with persistent hyperlactatemia, but the relative contribution of these factors has not been specifically addressed in comprehensive clinical physiological studies. Our goal was to determine potential hemodynamic and perfusion-related parameters associated with 6-hour lactate clearance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 36 publications
0
29
0
1
Order By: Relevance
“…The case of hyperlactatemia is paradigmatic. Although tissue hypoperfusion has been traditionally considered the most common cause of hyperlactatemia, there is increasing evidence for concomitant non-hypoxic and thus, non-flow dependent mechanisms [ 28 ],[ 29 ] that may influence the time course of lactate recovery rate. The distinction between these two scenarios (flow-responsive vs. non-flow dependent hyperlactatemia) should strongly impact the therapeutic approach [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The case of hyperlactatemia is paradigmatic. Although tissue hypoperfusion has been traditionally considered the most common cause of hyperlactatemia, there is increasing evidence for concomitant non-hypoxic and thus, non-flow dependent mechanisms [ 28 ],[ 29 ] that may influence the time course of lactate recovery rate. The distinction between these two scenarios (flow-responsive vs. non-flow dependent hyperlactatemia) should strongly impact the therapeutic approach [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Различия гемодинами ческого статуса в группах больных с III и IV стадиями демонстрируют реализацию токсического эффекта хи миотерапии [41][42][43]. Столь же вероятно, что гиперди намический тип кровообращения явился следствием реализации механизмов адаптации на этапно формиру ющийся дефицит ОЦК и изменения показателей кис лотно основного состояния [44].…”
Section: Resultsunclassified
“…The hyperdynamic type of blood circulation could also be a result of adaptation to deficit of blood volume and acid base disequilibrium [44].…”
Section: Resultsmentioning
confidence: 99%
“…23,24 There may be biphasic and/or variable responses to normalization of resuscitation variables (eg, rapid initial improvement in ScvO 2 , capillary refill time, and lactate clearance may be followed by slower trends thereafter) and further delays to normalization due to confounding by impaired hepatosplanchnic hypoperfusion. 25,26 Microcirculatory capillary blood flow (ie, use of sublingual orthogonal polarization spectral imaging) is commonly found abnormal among critically ill patients. Recent observational data have shown that disturbance in sublingual microcirculatory flow failed to correlate with patient survival, possibly because of a significant dissociation observed between sublingual and intestinal microcirculatory perfusion after fluid resuscitation.…”
Section: Optimizationmentioning
confidence: 99%